THE EFFECT OF SELF-AFFIRMATION ON ADOLESCENT ANXIETY IN FACING THE UNIVERSITY ENTRANCE SELECTION PROGRAM AT STATE MADRASAH ALIYAH 2 LEBAK - Fahmi Yusup Ependi; Osep Yasier Almunsiri; Lailatul Fadilah (Poltekkes Kemenkes Banten, 2026)
Background: Adolescence is the transition from childhood to adulthood, causing psychosocial changes, one of which is anxiety. Anxiety is a feeling of fear that something will happen due to anticipation of impending danger, thus helping people prepare to face threats. To overcome anxiety, self-affirmation can be used as a non-pharmacological measure to reduce anxiety in a person. Objective: The purpose of this study To determine the effect of self-affirmation on adolescent anxiety in facing college entrance selection at Madrasah Aliyah Negeri 2 Lebak. Method: The method used in this study was quantitative with a quasi-experimental design. The sampling method in this study was purposive sampling. The sample used in this study was 30 respondents. The instruments used in this study were the HARS questionnaire and the Self-Affirmation Standard Operating Procedure. Results: The results of the Simple Paired T-Test obtained a P-Value of 0.000 <the significant value (α = 0.05). Conclusion: The results of this study indicate that self-affirmation has an effect on adolescent anxiety.